Претсократовското разбирање на човекот - Калуѓеровиќ, Жељко; Донев, Дејан (Филозофски факултет во Скопје, УКИМ, 2020)
Western civilization, whose vision of cosmos is still prevailingly anthro- pocentric, finds the origin for its standing points in Judeo-Christian tradition and in the views of ancient Greek philosophers. In searching for antecedents of the vision of man as a being having a special status among other living beings, the focus of the study in this paper will be on the preserved fragments of first physicists. The authors have identified that indications of anthropo- centric approaches, despite structural hindrances of their concepts, may be found in Pythagoreans, Parmenides, Empedocles, Anaxagoras and Democri- tus. However, the Presocratics who most clearly anticipated the latter anthro- pocentric views was Alcmaeon from Croton, whose statement that the man is different from other living beings by being the only one that is capable of understanding while other living beings receive sensations but do not under- stand, represents, the authors concluded, an indication of both Aristotle’s and the statements of numerous subsequent thinkers that logos abilities may be allocated only to humans and that the man has ontological primacy in relation to other living beings.
Универзитет „Св. Кирил и Методиј“, Филозофски факултет – Скопје, Институт за филозофија TESTIMONIA PHILOSOPHICA Зборник во чест на проф. д-р Вера Георгиева по повод 70 години од раѓањето
Keywords: first physicists, practical wisdom i.e. thinking, sensation, ontological primacy, man